Understanding Mawdudi’s Thought: A Review of Religious, Social, Economic and Political Dimensions - Nadvi, Dr. Muhammad Junaid Nadvi; Dr. Muhammad Khalid Husain (Al Basirah, 2024)
This paper aims to provide a comprehensive understanding of the ideology of Sayyid Abul A’la Mawdūdī, a prominent Islamic scholar and thinker of the 20th century. Focusing on Mawdūdī’s religious, social, economic, and political ideas, the paper examines his contributions to Islamic thought and their relevance in contemporary perspectives. With a special focus, the paper explores Mawdūdī’s interpretations of Islam, his vision for society and governance, and his critiques of modern ideologies. Additionally, the paper examines the controversies surrounding Mawdūdī’s thought and offers insights gained from comparative analysis with other Islamic thinkers. By exploring Mawdūdī’s intellectual legacy, this paper seeks to contribute to a deeper understanding of Islamic thought and its implications for contemporary Muslim societies. It seems that over the coming years the comprehension and influence of his thoughts will grow within the field of contemporary Islamic social sciences and he will be recognized as one of the most influential thinkers in contemporary world of Islam.